If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2x + 8 = 10x + -7 Reorder the terms: 8 + 3x + 2x = 10x + -7 Combine like terms: 3x + 2x = 5x 8 + 5x = 10x + -7 Reorder the terms: 8 + 5x = -7 + 10x Solving 8 + 5x = -7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 8 + 5x + -10x = -7 + 10x + -10x Combine like terms: 5x + -10x = -5x 8 + -5x = -7 + 10x + -10x Combine like terms: 10x + -10x = 0 8 + -5x = -7 + 0 8 + -5x = -7 Add '-8' to each side of the equation. 8 + -8 + -5x = -7 + -8 Combine like terms: 8 + -8 = 0 0 + -5x = -7 + -8 -5x = -7 + -8 Combine like terms: -7 + -8 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 14.2=-6.8 | | -4x-2x-10=2x-34 | | 120-(-27)= | | 1/3x-15=10 | | 5-7[6-(4y-6)]= | | .80x=54.4 | | 200t+16t^2=625 | | x^2+18x+29=x^2-12x+36 | | 0/2 | | -4x+10=-5+18 | | 16t^2+200t+3=628 | | x+.09x=545 | | 2+3(3X-5)=5-3(2X+1) | | X+x+3=47 | | 3g+2(-5+4g)=1-g | | (b/-5)=11 | | 5g+3(-7+5g)=1-g | | (x/x-9)+9=(9/x-9) | | 3x+4=12x-13 | | 5(1-2w)+w=15 | | 6+1x=3x | | 16t^2+200t=-3 | | 3(x+4)=2x-12 | | 5-3[4-(3y-7)]= | | 136-(-11)= | | 7(-8+3h)=21h-49 | | 9m^3-7m^4+8m^7=0 | | 1/3p=2/5p+2/3 | | 6(x+2)/4=2x-5 | | 16t^2+200t=0 | | 8n-(2n+7)=17 | | 52+(-65)= |